EMPLOYMENT FATIGATION IN PHARMACEUTICAL INSTALLATION WORKERS IN BOGOR PMI HOSPITAL - Alia Keumala Muda, Cut; Fitri Purwati, Aida; Marti Ayu, Ira; Suryana, Ase (International Journal of Psychosocial Rehabilitation, 2020)
Fatigue is the body's protection mechanism so that the body is protected from further damage resulting in postrest recovery, this study was conducted to determine the description of work fatigue in Pharmacy Installation workers at the Bogor PMI Hospital in 2019. The design of this study uses quantitative with a Cross-Sectional approach. This research was conducted at the Bogor Red Cross Hospital with a population and sample of 69 respondents, sampling with a total sampling technique. Based on the results of the research showed that the highest Activity Fatigue (50,7%) low fatigue, the highest Motivation Fatigue (52,2%) low fatigue, the highest Physical fatigue (56,5%) high fatigue. It is expected that Pharmacy Installation workers at PMI Bogor Hospital in 2019 can maintain the policy that has been made and given special attention by the management to existing problems or be given training on the hazard of work fatigue.